Local English Students' Voices on Virtual Learning during Pandemic COVID-19 - S, Kartika (Lentera: Jurnal Ilmiah Kependidikan, 2022)
All universities in Indonesia are given the option to study at home with an online learning system, including UIN Raden Intan Lampung. Students' voices is a perspective from student towards something to know the success of it. This study aims to know students' voices on Online Learning during COVID-19 in some positive or negative ways. The research method used in this research is quantitative, with an online survey and purposive sampling. According to the results, 66 per cent of the total statements show that students positively perceive online learning acceptance. Students feel safer and more at ease, and they spend less money. However, some study aspects are lacking, such as unease in following the study, being active in class, and being enthusiastic about the study. Despite this, most students maintained positive relationships with other students, ate and slept well, and remained healthy throughout the pandemic. This recent study recommended that future research data sources be expanded to ensure more reliable research results.